2021
DOI: 10.1002/nop2.853
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ competency in Saudi Arabian healthcare context: A cross‐sectional correlational study

Abstract: is still challenged by the shortage of nurses despite the improvement of its healthcare system's overall efficiency (Tandon et al., 2000). According to the Ministry of Health (MOH), Saudis only constitute 38% of the total workforce, in which 32.3% are nurses (Almalki et al., 2011). In 2012, the MOH reported that expatriate nurses accounted for 63.82% of the Saudi Arabia nursing workforce, most were from the Philippines or India. Because of the diverse nursing preparations of nurses working in Saudi Arabia, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 68 publications
3
16
0
Order By: Relevance
“…Similar to our findings, a study among nurses in Saudi Arabia reported a lower level of competence with respect to critical thinking [ 3 ]. Critical thinking among nursing professionals especially in emergency care plays a very crucial role in decision-making for patient management and clinical judgment in a critical situation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our findings, a study among nurses in Saudi Arabia reported a lower level of competence with respect to critical thinking [ 3 ]. Critical thinking among nursing professionals especially in emergency care plays a very crucial role in decision-making for patient management and clinical judgment in a critical situation.…”
Section: Discussionsupporting
confidence: 91%
“…There is a close relationship between the clinical competence of nurses and the quality of care [ 2 ]. Lack of knowledge and the variation in the professional competencies in different skills such as critical thinking and research aptitude, clinical care, leadership, legal and ethical practices, professional development, interpersonal relationships can lead to lowering the quality of healthcare services to care recipients [ 3 ]. There is a lack of high-quality studies exploring the clinical competence of nurses in critical areas such as emergency department.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demands of the profession require nurses to be particularly adept and mindful of their responsibilities without sacrificing one's competence toward professional obligations. Be it in the field of hospital and academic practice, for instance, they feel the need to completely concentrate on their assigned roles with the consideration of competency and safety in practice (Feliciano et al, 2021;. Lastly, the vigor domain is characterized by engagement in work with a high level of energy and mental resilience demonstrating behavior-energetic components (Decuypere and Schaufeli, 2020;Aldeeb and El-Demerdash, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The care for older adults stems from the various needs that they need to cope with and become resilient to the challenges of aging (Feliciano et al, 2022b). The rapidly aging population becomes an urgent health concern due to the crucial need for competent healthcare providers while maintaining the safe nursing practice for patient safety outcomes (Feliciano et al, 2021;2019;CDC, 2019) and the risk for co-morbidities among older adults is implied along with the concept related with "everlasting caregiving" (Sakakibara et al, 2015).…”
Section: Discussionmentioning
confidence: 99%